Sequencing of emerging canine distemper virus strain reveals new distinct genetic lineage in the United States associated with disease in wildlife and domestic canine populations. Issue 1 (December 2015) - Riley, Matthew; Wilkes, Rebecca
Abstract Background Recent outbreaks of canine distemper have prompted examination of strains from clinical samples submitted to the University of Tennessee College of Veterinary Medicine (UTCVM) Clinical Virology Lab. We previously described a new strain of CDV that significantly diverged from all genotypes reported to date including America 2, the genotype proposed to be the main lineage currently circulating in the US. The aim of this study was to determine when this new strain appeared and how widespread it is in animal populations, given that it has also been detected in fully vaccinated adult dogs. Additionally, we sequenced complete viral genomes to characterize the strain and determine if variation is confined to known variable regions of the genome or if the changes are also present in more conserved regions. Methods Archived clinical samples were genotyped using real-time RT-PCR amplification and sequencing. The genomes of two unrelated viruses from a dog and fox each from a different state were sequenced and aligned with previously published genomes. Phylogenetic analysis was performed using coding, non-coding and genome-length sequences. Virus neutralization assays were used to evaluate potential antigenic differences between this strain and a vaccine strain and mixed ANOVA test was used to compare the titers. Results Genotyping revealed this strain first appeared in 2011 and was detected in dogs from multiple states in the Southeast region of the United States. It was the main strain detected among the clinical samples that were typed from 2011–2013, including wildlife submissions. Genome sequencing demonstrated that it is highly conserved within a new lineage and preliminary serologic testing showed significant differences in neutralizing antibody titers between this strain and the strain commonly used in vaccines. Conclusion This new strain represents an emerging CDV in domestic dogs in the US, may be associated with a stable reservoir in the wildlife population, and could facilitate vaccine escape.